Reduction of Coxiella burnetii Prevalence by Vaccination of Goats and Sheep, the Netherlands - Lenny Hogerwerf; René van den Brom; Hendrik I.J. Roest; Annemarie Bouma; Piet Vellema; Maarten Pieterse; Daan Dercksen; Mirjam Nielen (Emerging Infectious Diseases, 2011)
Recently, the number of human Q fever cases in the Netherlands increased dramatically. In response to this increase, dairy goats and dairy sheep were vaccinated against Coxiella burnetii. All pregnant dairy goats and dairy sheep in herds positive for Q fever were culled. We identified the effect of vaccination on bacterial shedding by small ruminants. On the day of culling, samples of uterine fluid, vaginal mucus, and milk were obtained from 957 pregnant animals in 13 herds. Prevalence and bacterial load were reduced in vaccinated animals compared with unvaccinated animals. These effects were most pronounced in animals during their first pregnancy. Results indicate that vaccination may reduce bacterial load in the environment and human exposure to C. burnetii.